Am I prepared for Calculus? An action-research study of female students emerging from patriarchy - Waheed, Saira; Pilotti, Maura A. E.; AbdelSalam, Hanadi M. (Frontiers in Education, 2024)
In this action-research study, the inquiry phase aims to examine the extent to which self-evaluations of Math prerequisite competency relate to the past and current Math performance of STEM female students from a society emerging from strict patriarchy. Its ancillary aim is to determine whether attitudes toward Math and its instruction and assessment are related to past and current performance. Undergraduate Engineering and Computer Science students were surveyed at the start of a Calculus course. As per earlier courses, Calculus was taught through an inquiry-based learning model. Findings illustrated that Math prerequisite competency was underestimated relative to past performance but accurate relative to current performance. Positive attitudes towards Math were correlated with past but not current performance. Students’ preferences for modes of instruction and assessment suggested areas of improvement. During the pragmatic phase of the study, these findings informed instructional changes to enhance Math learning in Engineering and Computer Science.